PREMATURITY AS A RISK FACTOR FOR THE DEVELOPMENT OF SEVERE VIRAL BRONCHITIS IN CHILDREN UNDER 3 YEARS OF AGE (Actas Médicas (Ecuador), 2022)
INTRODUCTION: Bronchiolitis is an important cause of respiratory disease in children under 3 years of age and represents one of the main causes of hospitalization in infants and children under 5 years of age. Risk factors leading to the development of severe disease include: age less than 12 weeks, history of prematurity ≤36 SG, and low birth weight; In Ecuador, acute bronchiolitis ranks 9th among the 10 main causes of infant morbidity in children under 1 year of age.METHODOLOGY: It is a relational, observational, retrospective, bivariate cross-sectional study.The information was collected from the medical records of patients who were admitted for emergency and electively who were hospitalized at the Roberto Gilbert Hospital with a definitive diagnosis of bronchiolitis in the period from January 2017 to December 2019.RESULTS: Of the 278 patients in the sample, 21.58% (60 patients) had a history of prematurity, and 78.42% (218 patients) were full-term children with bronchiolitis. Of the 100% of premature infants, 53% developed moderate bronchiolitis, 32% severe bronchiolitis, and 15% mild bronchiolitis.CONCLUSION: The proposed hypothesis turned out to be false, finding no association between the history of prematurity with the development of severe bronchiolitis. Pediatric patients considered in the study developed bronchiolitis of similar severity, the most common being moderate, regardless of whether they were born prematurely or at term.